Decision Support System For Election Of Members Unit Patients Pamong Praja - Haswan, Febri (International Journal of Artificial Intelligence Research, 2017)
Civil Service Police Unit (municipal police) is part of the area in the enforcement of legislation and arrangements for public order and public tranquility . Decision Support System or DSS ( Decision Support System ) is a computer -based information systems whose main goal is to help decision -making utilize data and models to solve the problems that are unstructured and semi- structured . In accepting prospective members of the previous municipal police PSDM section sorting and selecting applicants one by one entering the data so that the data obtained is not clear didapt results of each participant. By using Fuzzy Multiple Attribute Decision Making (FMADM) is used to find an alternative from a number of alternatives to optimize certain criteria , while the Simple Additive Weighting method (SAW). SAW method is often also known term weighted summation method . The basic concept is to find a method SAW weighted summation of the performance ratings of all the attributes of each alternative.